Sequential H2-optimization procedure for robust flight control law's parametric synthesis - Tunik, А. А.; Krinetskaya, Е. М. (Proceedings of National Aviation University (archive), 1999)
Sequential iterative procedure of Flight Control Law (FCL) robust parametric optimization is proposed. The 1st step of this procedure is the application of the convex optimization procedure with quadratic performance index whose coefficients are chosen on the basis of airworthiness requirements. The steps are made for enlargement of the stability domain in the space of variable parameters applying aforementioned procedure for composite performance index constructed from components, which depend on the influence of parametric disturbances. Practical example illustrates efficiency of this procedure